Measuring Street Network Efficiency and Block Sizes in Superblocks—Addressing the Gap between Policy and Practice - Rim Anabtawi; Martin Scoppa (Buildings, 2022)
This paper uses quantitative methods to evaluate the application of street connectivity policies stated by Abu Dhabi’s Urban Planning Council (UPC) on newly developed projects. The evaluation of the study was performed by measuring efficiency, i.e., how short and direct are paths between residential and nonresidential destinations to understand the ability of street networks to support sustainable transportation modes in the Capital District project. Efficiency is measured in twelve neighborhoods of the Capital District using Pedestrian Route Directness (PRD), a metric that meets Estidama—Abu Dhabi Green Rating System—walkability standards. Observation and analysis of the current stage of development show that more than 58% of the neighborhoods failed the route efficiency test to connect residential plots to one another. In addition, more than 40% of the neighborhood’s residential plots could not efficiently connect to nonresidential plots. The study includes recommendations for policymakers and project developers to enhance the street infrastructure to correlate with Estidama ratings by taking advantage of sikkak, the alleyways system that is found in other neighborhoods in the city. Significantly, recommendations are based on rigorous quantitative analyses that can be used for implementation in real-world projects, thus strengthening the connection between policy and practice.